Service needs of adolescent parents in child welfare: Is an evidence based, structured, in-home behavioral parent training protocol effective?☆ - Hubel, Grace S. (Child Abuse Negl, 2018)
SafeCare is an evidence-based behavioral parent training intervention that has been successfully implemented in multiple state child welfare systems. A statewide implementation in Oklahoma established the effectiveness of SafeCare with a diverse group of parents, which included adolescent parents under 21 years of age, a particularly at-risk group. The current study examined whether SafeCare is also effective for this subsample of 294 adolescent parents with regard to child welfare recidivism, depression and child abuse potential, and attainment of service goals. Post-treatment adolescent parent ratings of program engagement and satisfaction were also examined. Among the subsample of adolescent parents, the SafeCare intervention did not result in significantly improved outcomes in terms of preventing recidivism or reduction in risk factors associated with child abuse and neglect as compared to child welfare services as usual. Further, no significant differences in program engagement and satisfaction between SafeCare and services as usual were detected. These findings shed light on the potential differences in program effectiveness between adolescent and adult parents, and the need for future research to rigorously evaluate the effectiveness of behavioral parenting programs with adolescent parents.